Regional and global impacts of the 2007 Port-of-Spain Declaration on noncommunicable diseases - John Kirton; W. Andy Knight; C. James Hospedales; Dinah Hippolyte; Julia Kulik (Pan American Health Organization, 2019)
Objective. To assess how well Caribbean regional institutions (RIs) met their commitments from the 2007 Port-of-Spain Summit (POSS) declaration on noncommunicable diseases (NCDs), and evaluate the POSS impact on the United Nations High-level Meeting (HLM) on NCDs in 2011 (2011 HLM), HLM NCD review in 2014 (2014 HLM), World Health Organization's 2025 NCD targets (2025 WHO), and 2030 Sustainable Development Goals (SDGs) agreed upon in 2015. Methods. This study uses a method developed by the University of Toronto's Global Governance Program to measure institutions' compliance with commitments from a summit and the match with commitments from earlier summits. This approach was supplemented using data from published literature, primary documents, and semistructured key informant interviews to detail how and why Caribbean RIs met the 2007 POSS commitments, how the 2007 POSS commitments led to compliance, and how the 2007 POSS influenced international NCD commitments. Results. Caribbean RIs implemented the 2007 POSS commitments better when they had more public legitimacy, when their missions aligned with those commitments, and when more resources were available to them. Implementation constraints arose from multiple, sometimes competing, interests of the decision-making and national implementing bodies of the Caribbean Community (CARICOM). Internationally, the early, expanding efforts of the POSS pioneers had an initially important but subsequently diminishing impact on the HLMs. Conclusions. For the Caribbean region, the Caribbean Public Health Agency should be funded to lead strengthened Caribbean RIs in coordinated action on NCDs. At the international level, the United Nations should embed NCDs in a "whole-of-global-governance" approach, monitor implementation annually, foster transregional partnerships on NCD-related themes, engage civil society, and support regular regional and global summits to enhance implementation and improvement, aimed at future HLMs on NCDs, the 2025 WHO targets, and the SDG NCD targets.